2014
DOI: 10.3329/bjsr.v26i1-2.20228
|View full text |Cite
|
Sign up to set email alerts
|

Level of noise pollution at different locations in Tangail municipal area, Bangladesh

Abstract: The study was carried out to ascertain the level of noise pollution at different locations in Tangail municipal area. For this purpose noise levels were measured at different locations at different periods of the day. At all the locations the level of noise were found to be higher than the acceptable level. The intensity of noise was found lower with increasing distance from the road side. The noise level on the main road near hospital, shopping center and bazars was above the standard level recommended by MoE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…It is observed that respondents with various age groups, gender, respondent types, and staying hours in a noisy environment were all significant predictors of noise-related health issues. Several studies were conducted in different metropolitan areas of Bangladesh to evaluate the causes and effects of sound pollution on human health (Haq et al, 2012;Hoque et al, 2013;Islam et al, 2015;Jahan et al, 2016;Rahman et al, 2016;Sultana et al, 2020;Uddin et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is observed that respondents with various age groups, gender, respondent types, and staying hours in a noisy environment were all significant predictors of noise-related health issues. Several studies were conducted in different metropolitan areas of Bangladesh to evaluate the causes and effects of sound pollution on human health (Haq et al, 2012;Hoque et al, 2013;Islam et al, 2015;Jahan et al, 2016;Rahman et al, 2016;Sultana et al, 2020;Uddin et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…This study found that different types of vehicles on the roadway are the main cause of sound pollution in the study area. An earlier study showed that motor vehicles are the main source of high levels of noise (Aftab et al, 2007;Carrier et al, 2016;Clark and Paunovic, 2018;Hoque et al, 2013;Rahman et al, 2022;Sultana et al, 2020). The uncontrolled traffic across the metropolitan area is responsible for creating sound pollution in Dhaka city (Bint and Rahman, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies were conducted in different cities in Bangladesh in order to assess noise level and its impact on human health. In mixed areas of Dhaka city, at different locations in Tangail municipal area, Jessore city, Chittagong city corporation and Mymensingh Sadar Upazila the noise level was found to exceed the accepted recommended noise level set by DOE [9], [22], [10], [11], [12].It was cited earlier, Leq and Lnp is an important descriptor related to the effect of noise pollution on human health. The values of various noise parameters L10, L90, Leq and Lnp also became higher in many cities in Bangladesh [22], [24].…”
Section: Discussionmentioning
confidence: 99%
“…This uncontrolled movement of traffic throughout the city is responsible for roadway noise in Dhaka city [15]. Motor vehicles are the main source of high noise levels [10], [14]. The highest average noise level was observed during day time as of high traffic flow in peak working hours.…”
Section: Discussionmentioning
confidence: 99%
“…In Bangladesh, average noise levels in healthcare buildings exceeds 45 dBA, which is the allowable limit set by Environmental Conservation Act -1995 (ECA '95) and Environmental Conservation Rules 1997 (ECR '97) (Haq et al, 2012). Some examples of these cases are given below (Haq et al, 2012, Rahman et al, 2016, Hoque et al, 2013, Alam et al, 2006. Inside any healthcare facilities, sound may generate from different devices present in its surroundings such as alarms, beepers, machines, rolling carts, furniture movement, Heating Ventilation and Air Conditioning (HVAC) systems as well as from animate objects such as human conversation (Clarke, 2011).…”
Section: Introductionmentioning
confidence: 99%